Christianity as a Culture of Mobility: A Case Study of Asian Transient Migrants in Singapore - Gomes, Catherine (Archīum Ateneo, 2024)
More than ever before, the global and transnational movements of young people for work and study have become part of everyday life. Yet there is very little research on this phenomenon in relation to how actors in transience create strategies to cope with being away from home nation (place of birth and/or citizenship) and from family. As part of the findings of a larger international study on the identities, social networks and media/ communication use of transient migrants, researchers found that Christianity featured prominently during life in transience for Asian respondents. This paper thus puts forward the notion that Christianity may well function as a culture of mobility by looking at its significance to Asian “foreign talent” transient migrants in Singapore. Through face-to- face interviews with fifty-seven Asian working professionals and international students, this paper found thirty that not only identified themselves as Christian, but whose social networks were also made up of Asian foreign talent transient migrant Christians. This paper thus suggests that Asian foreign talent transient migrants turn to Christianity as a way of coping with everyday life in transience. The Christian groups they join allow them to create a sense of community while being away from the home nation. This sense of community however is with other transient migrants, rather than with locals.